Bird-ringing results in Slovakia in 2023 - Michal Jenčo; Roman Slobodník; Michal Baláž (Tichodroma)
In 2023, 59 ringers ringed altogether 72 658 birds, belonging to 151 species. Of them, the Great Tit (Parus major, 9 011 ind.), Blackcap (Sylvia atricapilla, 8 209 individuals), Barn Swallow (Hirundo rustica, 7 192 ind.), European Robin (Erithacus rubecula, 5 364 ind.) and Blue Tit (Cyanistes caeruleus, 5 110 ind.) were the five most frequently ringed species. The most numerous birds ringed as nestlings were the Great Tit (2 769 ind.), White Stork (Ciconia ciconia, 1 302 individuals), Common Kestrel (Falco tinnunculus, 890 ind.), Collared Flycatcher (Ficedula albicollis, 491 ind.) and Barn Swallow (393 ind.). Overall, nestlings accounted for approximately 10% of all ringed birds. In 2023, 720 recoveries from abroad were registered. Of these, 210 individuals were ringed abroad and re-trapped in Slovakia, while 510 were individuals ringed in Slovakia and re-trapped abroad. The longest-distance recovery involved a Lesser Spotted Eagle (Clanga pomarina) found in Zambia, 7 081 km away from its ringing site in Slovakia. The record for longevity was held by a Black Stork (Ciconia nigra), which was re-encountered 22 years after being ringed.